The Charter, Amendments, and Acts of the Legislature Relating to the Municipal Court, and the Ordinances of the City of Lewiston, Together with the Boundaries of the Several Wards, Regulations Respecting Gunpowder, and an Abstract of the Laws Relating to the Powers and Duties of Cities and Towns Page 43, Image 43 (1873) §§ 1-3 - (:unkn) unknown (General Publisher, 1873)
No person shall keep or have in any shop, store, dwelling house or tenement, in the city of Lewiston, at any one time a larger quantity of gun-powder than one pound, unless he is licensed by the mayor and aldermen to keep and sell gunpowder, or except as hereinafter provided. § 2. It shall not be lawful for any person or persons to sell any gunpowder which may at the time be within said city, in any quantity, by wholesale or retail, without having first obtained from the mayor and aldermen a license to sell gunpowder, and every license shall be written or printed, and duly signed by the mayor, on a paper upon which shall be written or printed a copy of the rules and regulations established by the city relative to keeping, selling and transporting gunpowder within said city; and every such license shall be in force one year from the date thereof, unless revoked by the mayor and aldermen; but such license may, prior to its expiration, be renewed by an endorsement thereon by the mayor, for the further term of one year, and so from year to year, provided, always, that it may at any time be rescinded or revoked by the mayor and aldermen, for good and sufficient reasons. § 3. Every person who shall receive a license to sell gunpowder, as aforesaid, shall pay for the same to the treasurer of the city the sum of three dollars, and for each renewal of the same, the sum of one dollar.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER